Determinants of prebiotic vegetable consumption: the extended theory of planned behaviour - V. J. V. Broers; S. Van den Broucke; O. Luminet (BMC, 2020)
Abstract Background Prebiotic vegetables such as leek and salsify may contribute to preventing obesity by changing the composition of the gut microbiota. To increase consumption of prebiotic vegetables, the aim of the study was to document the prevalence and determinants of (prebiotic) vegetable consumption. Methods An online, correlational questionnaire was administered to participants using a mixed approach (1078 online, 200 face-to-face). Participants were a representative sample (gender, age, level of education, province, population density and (un)employment) of 1278 adults of the Walloon region in Belgium. The frequency and determinants of prebiotic vegetable consumption were measured using an extension of the Theory of Planned Behaviour including habits, actual control and compensatory health beliefs. Descriptive analyses were performed followed by hierarchic multiple regression analyses. Results The descriptive results showed that for all categories (leek, salsify, vegetables in general) an improvement in both intentions and prevalence of the actual behaviour is necessary to experience the health benefits of (prebiotic) vegetables. Intentions and habits were important predictors of consumption for all types of vegetables, and hedonic attitudes and subjective norms were important predictors of intention. Perceived control and rational attitudes were predictors of intention to consume only for vegetables in general. Finally, environmental factors such as price, availability and actual control predict consumption but their influence differs depending on the vegetable. Conclusions The findings can be used to inform interventions that aim to increase (prebiotic) vegetable consumption. Umbrella terms such as 'healthy food' or 'vegetables' do not capture the differences between the specific foods regarding the demographic and socio-psychological determinants of their consumption. This is the first research to investigate the determinants of prebiotic vegetable consumption.